A new species of black fly (Diptera: Simuliidae) in the Simulium (Simulium) multistriatum species-group from Thailand - Thaijarern, Jiraporn; Wongpakam, Komgrit; Kangrang, Anongrit; Pramual, Pairot (Zootaxa, 2019)
A new black fly species of the Simulium multistriatum species-group of the subgenus Simulium Latreille is described from the mountainous area in northeastern Thailand, based on morphology and mitochondrial DNA sequences. The new species is morphologically similar to S. laui Takaoka and Sofian-Azirun and S. lacduongense Takaoka and Ya’cob originally described from Vietnam, S. fenestratum Edwards originally described from Indonesia and S. chaliowae Takaoka and Boonkemtong originally described from Thailand, but can be distinguished in the adult stage by the number of upper eye facets and globular shape of the spermatheca and in the pupal stage by the cocoon and shape of thoracic tubercles. Genetic distance and phylogenetic analyses of mitochondrial cytochrome c oxidase I sequences differentiated the new species from other members of S. multistriatum species-group. All specimens of the new species formed a monophyletic clade with strong support in all phylogenetic analyses. The minimum interspecific genetic distance of 4.9% is considerably greater than the new species maximum intraspecific genetic distance (2.7%).